Economic Warfare : Enduring Its Impact - Muhammad Faizal Abdul Rahman (2019)
A multipolar world comprising several political, military, technological and economic spheres of influence that arise from irreconcilable geopolitical rivalries is beginning to take shape. Besides influencing states’ policymaking, these rivalries can have trickle-down effects on industries and ordinary people.